Fabrication of thin targets for nuclear reaction studies at IUAC. (October 2017) - Banerjee, T.; Abhilash, S.R.; Kabiraj, D.; Ojha, S.; Umapathy, G.R.; Shareef, M.; Laveen, P.V.; Duggal, H.; Amarnadh, R.U.; Gehlot, J.; Nath, S.; Mehta, D.
Abstract: Thin, durable, uniform, isotopic targets of 193 Ir, 187 Re, 182 W, 181 Ta, 175 Lu and 169 Tm of thicknesses ∼80 μ g/cm 2, 60 μ g/cm 2, 70 μ g/cm 2, 175 μ g/cm 2, 110 μ g/cm 2 and 270 μ g/cm 2, respectively, have been fabricated on carbon backing by physical vapor deposition technique for nuclear reaction studies at Inter University Accelerator Centre (IUAC), New Delhi. Preparation of very thin self-supporting targets of these elements is non-reproducible. A carbon backing thickness of ∼22 μ g/cm 2 was achieved. For the targets of refractory metals ( 193 Ir, 187 Re, 182 W, 181 Ta) e-gun evaporation was used. The lanthanide targets ( 175 Lu, 169 Tm) were fabricated using: (a) e-gun (for nat C backing), (b) resistive heating (for source material deposition) and (c) e-gun evaporation (for nat C capping) methods successively, without breaking the vacuum. Fabrication details of these targets, with actions taken against the challenges (peeling off, heat damage etc.) experienced during fabrication, are reported. No high Z contamination is found in any of the targets by RBS and XRF analysis. Highlights: Thin, durable, uniform, isotopic targets of 193 Ir, 187 Re, 182 W, 181 Ta, 175 Lu and 169 Tm have been fabricated by physical vapor deposition technique. Preparation of very thin self-supporting targets of these elements are non-reproducible. Lanthanide targets ( 175 Lu, 169 Tm) were sandwiched between two thin carbon layers to protect them from tarnishing in air. Use of carbon coated glass slides instead of carbon foils as a substrate, resulted in high productivity and longer target lifetime. No high Z contamination is found in any of the targets.